Segregación laboral por género. (2016)
The text examines the changes in sectorial and occupational segregation by sex in Colombia and its metropolitan areas between 2000 and 2015. For this purpose, it is used the Duncan and Duncan and Karmel-MacLachlan indexes, which allow to study the way in which labor segregation evolves, during a certain period. Subsequently, the local segregation curves are used to show the ratio between the percentage of total employment accumulated and the percentage of cumulative employment of each group, in order to put in evidence which group is more segregated and in which aspect. The results of the investigation indicate that labor segregation exists for branch of economic activity and occupational position, for the entire period of analysis, although in general it is evidenced a slight decrease of the levels in the time of study.